The Influence of Brand Image and Lifestyle on Purchase Decisions - Putri Jamila; Salim Siregar (Almana : Jurnal Manajemen dan Bisnis, 2022)
In recent years, a growing sector in the food and beverage industry is coffee shops. Of the many culinary businesses, coffee shops are currently the prima donna. At this time, coffee shops have become a phenomenon that affects the lifestyle of the Indonesian people. So this research was conducted to obtain empirical evidence and find clarity on the phenomenon and conclusions about the influence of Brand Image and Lifestyle variables on the Purchase Decision of Starbucks Coffee Jababeka Cikarang. This research was conducted using descriptive and verification methods, namely knowing, explaining, and analyzing. The sample in this study was 100 respondents, where respondents were selected using the accidental sampling method. There is a correlation between Brand Image and Lifestyle of 0.634, meaning that Brand Image and Lifestyle have a relationship with solid criteria. There is a partial influence between Brand Image on the Purchase Decision of Starbucks Coffee Jababeka Cikarang. There is a simultaneous influence between Brand Image and Lifestyle on the Purchase Decision of Starbucks Coffee Jababeka Cikarang of 0.562 or 56.2%, while the remaining 43.8% is influenced by variables not examined.